Speech and utopia - Kelly, M; Michael G. Kelly (2002)
﻿ The thesis argues that a certain 'locus' of poetry is perceptible diachronically in the French literary field of the 20th Century and that this locus (elusive, fragmented, multilayered) may be meaningfully focused upon via the interaction of the questionings centered around the terms 'speech' and 'utopia'. In the introduction an argument is made for the conceptual validity of the term 'utopia' in relation to the diverse literary practices accruing around the pole of the 'poetic', which results in the derivation of the idea of a Utopian dynamic - a vectoral addition to the conventionally static, figure-bound 'utopia'. Concentrating on three poets (Victor Segalen, René Daumal and Yves Bonnefoy) from three distinct generations and periods (pre-WWI, inter-War and post-WWII) which are standardly represented as discontinuous, the thesis proposes an analysis, ordered along three canonical sub-divisions of the Utopian preoccupation (which are three distinct modalities of Utopian space), of the Utopian dynamic argued to be characteristic of the work of poetic writing. The three parts of the thesis thus examine the 'poetic' as occurring within social space (lieu commun), physical space (haut lieu) and textual space (non lieu) over the combined duration of the corpus. Arguing for an intelligible continuity of preoccupation among the three poetic oeuvres discussed, the thesis concludes that that continuity enables, in return, a modification of our understanding of the Utopian, of which a lucid practice of poetic writing can thus become the embodiment. Utopia, from being a synonym for illusionment in a century at all times supremely alive to the need for irony, becomes a creative embrace of disenchantment. The point of resolution (poetic foundation) at each stage in the individual oeuvres analysed being the ongoing representation of the 'human' as inner and outer limit to the poetic subject's practice and to the aspiration from which it moves.